1994
DOI: 10.1021/jm00043a014
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship Studies of Central Nervous System Agents. 13.4-[3-(Benzotriazol-1-yl)propyl]-1-(2-methoxyphenyl)piperazine, a New Putative 5-HT1A Receptor Antagonist, and Its Analogs

Abstract: A new set of 4-alkyl-1-(o-methoxyphenyl)piperazines containing a terminal benzotriazole fragment were synthesized, and their 5-HT1A and 5-HT2 affinity was determined. It was shown that the benzotriazole moiety contributes to both the 5-HT1A and 5-HT2 receptor affinity. It was demonstrated in several behavioral models that 4-[3-(benzotriazol-1- yl)propyl]-1-(2-methoxyphenyl)piperazine (11) is a new, potent presynaptic and postsynaptic 5-HT1A receptor antagonist. However, it is not selective for 5-HT1A versus al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…Statistical values of the above Table 3. Structure, 5-HT 1A receptor affinities, migration decrease (∆R f ) and the calculated log P data of the tested compounds 1-22 a Data taken from the literature: 1-3 (Mokrosz et al, 1994b), 4, 5, 9, 10 (Paluchowska et al, 1999), 7 (Mokrosz et al, 1994c), 8 (Mokrosz et al, 1994a), 11-15 (Paluchowska et al, 2001), 16, 17 (Paluchowska et al, 2003a,b), 18 (Byrtus et al, 1996), 19 (Byrtus et al, 2001), 20-22 (Chlon et al, 2001). b log P c was calculated using a PrologP 5.1 program (CompuDrug Ltd., Hungary).…”
Section: Resultsmentioning
confidence: 99%
“…Statistical values of the above Table 3. Structure, 5-HT 1A receptor affinities, migration decrease (∆R f ) and the calculated log P data of the tested compounds 1-22 a Data taken from the literature: 1-3 (Mokrosz et al, 1994b), 4, 5, 9, 10 (Paluchowska et al, 1999), 7 (Mokrosz et al, 1994c), 8 (Mokrosz et al, 1994a), 11-15 (Paluchowska et al, 2001), 16, 17 (Paluchowska et al, 2003a,b), 18 (Byrtus et al, 1996), 19 (Byrtus et al, 2001), 20-22 (Chlon et al, 2001). b log P c was calculated using a PrologP 5.1 program (CompuDrug Ltd., Hungary).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the LLR in rats, induced by the wellknown 5-HT 1A receptor agonist 8-OH-DPAT, depends on stimulation of postsynaptic 5-HT 1A receptors [14,17]. Furthermore, this symptom is sensitive to 5-HT 1A receptor antagonists, including WAY 100635, MP3022, and NAN-190 [3,11,18]. Hence, the ability of the tested compounds to inhibit 8-OH-DPAT-induced LLR was regarded as antagonistic activity.…”
Section: Pharmacologymentioning
confidence: 99%
“…The cis and trans stereoisomers were successfully separated and pharmacologically characterized. The previously described flexible analogs 6a -9a were used as reference structures [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the w-bromoalkyl derivatives 33 and 34 were prepared by reacting 28 with an excess of the suitable oligomethylene dibromide in the presence of KF/Al 2 O 3 prepared according to Texier ± Boullet et al [30] (Method B). This procedure has been used before by Mokrosz et al [23] and by us [14] for the preparation of 1-and 2-(4-bromobutyl)benzotriazole. The 1-and 2-substituted isomers were separated as usual.…”
mentioning
confidence: 99%
“…Of the additional known compounds included in this study, 22 and 25 had been prepared before by Mokrosz et al [23] by reacting the unsubstituted benzotriazole with 1-(3-bromopropyl)-4-(2-methoxyphenyl)piperazine; and compounds 23 and 26 had been prepared by the same authors from the unsubstituted benzotriazole. In the present work, we found it convenient to synthesize compounds 22 and 25 via the 1-and 2-(3-tosyloxypropyl)benzotriazole in analogy to Method A, especially since we have prepared the required tosylates before [31].…”
mentioning
confidence: 99%